Play, Playbour or Labour? The Relationships between Perception of Occupational Activity and Productivity among Streamers and YouTubers. - Törhönen Maria; Hassan Lobna; Sjöblom Max; Hamari Juho (United States, 2025)
The increasing digitalization and gamification of different aspects of our lives has blurred the line between what we consider work and play. Therefore, our productivity may increasingly depend on how we negotiate and view our occupations and work. Through an online survey (n=382), this study examines the relationship between the perception of online video content creation as either work, play or equally as both, and the activities and income of these video content creators (streamers and YouTubers). The results indicate that those who view their content creation as work had the highest levels of activity and income, whereas those who associated their content creation with play, earned more income than those who regard their content creation equally as play and work. The results demonstrate the emergence of new forms of digital entrepreneurial practices in the work-oriented group, but also the highlight the increasing workification of our play activities.
Proceedings of the 52nd International Conference on System Sciences